(untitled) (Principles and Practice of Clinical Research, 2021)
Objective: Estimate the economic burden of type 1 diabetes (T1D) in the Dominican Republic and its impact on treatment adherence and patients’ quality of life (QoL). Materials and Methods: Cross-sectional observational study about T1D treatment cost and adherence plus patients QoL. The total monthly cost of treatment regimes was calculated through microcosting analysis and correlated with a national minimum wage (NMW) and average household income. Sociodemographic, clinical, treatment adherence, and QoL data were obtained through an online questionnaire. In an exploratory approach, all variables were compared with the categorization of household income. Results: Fixed doses (FD) regime has the lowest cost (46% of the NMW) and continuous subcutaneous insulin infusion (CSII) the highest (540% of the NMW). The lower household income group had less insurance coverage (P= 0.034), purchased fewer diabetes management supplies for cost-related reasons (P= 0.014), performed less glycemic monitoring (P= 0.016), and had more cost-related factors limiting appropriate treatment and follow-up (P= 0.030). Also, the FD treatment modality predominated in this group, while Multiple Daily Injections and constant subcutaneous insulin injection prevailed in the higher income group (P= 0.005). The QoL mean scores were 31.63 (SD 8.02) in the lower-income group and 32.52 (SD 8.81) in the higher-income one. Conclusions: T1D has a high monthly economic impact, potentially worsening treatment adherence and QoL, especially in the lower socioeconomic status population. Efforts must be made by the healthcare system to enhance the economic support and management of this disease. KEYWORDS: Type 1 diabetes, Microcosting, Dominican Republic, Public Health, Treatment adherence.